Assessment of the quality of dna extracted by two techniques from Mycobacterium tuberculosis for fast molecular identification and genotyping - Miyata, Marcelo [UNESP]; Santos, Adolfo Carlos Barreto [UNESP]; Mendes, Natália Helena; Cunha, Eunice Atsuko; Melo, Fernando Augusto Fiúza de; Leite, Clarice Queico Fujimura (Sociedade Brasileira de Microbiologia, 2011)
We report a comparative study of two DNA extraction techniques, thermolysis and chemical lysis (CTAB), for molecular identification and genotyping of M. tuberculosis. Forty DNA samples were subjected to PCR and the results demonstrated that with thermolysis it is possible to obtain useful data that enables fast identification and genotyping.
Keywords: DNA extraction; Mycobacterium tuberculosis; thermolysis; CTAB